1969
DOI: 10.1542/peds.44.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Infant Injuries: Accident or Abuse?

Abstract: Observations were made of 146 children who were accidentally injured or abused, and 113 children were studied in detail. The injuries of the abused group tended to be more severe and to be followed by serious sequelae more often than those of the accidentally injured, but the two groups, accident and abuse, were difficult to differentiate on the basis of history alone. Other findings such as developmental retardation, patient's ordinal position, family density, and ability to cope with stress were more useful.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1970
1970
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Various other studies enter figures from their own samples, generally repeating Kempe's findings (Birrell & Birrell, 1968;Cameron, Johnson, & Camps, 1966;Ebbin, Gollub, Stein, & Wilson, 1969;Elmer & Gregg, 1967;Gregg & Elmer, 1969;Heifer & Pollock, 1967;Johnson & Morse, 1968;Nurse, 1964;Schloesser, 1964;Skinner & Castle, 1969). Elmer (1967) and Young (1964) add to Kempe's findings the factors of social and economic stress, lack of family roots in the community, lack of immediate support from extended families, social isolation, high mobility, and unemployment.…”
Section: Demographic Characteristicsmentioning
confidence: 82%
“…Various other studies enter figures from their own samples, generally repeating Kempe's findings (Birrell & Birrell, 1968;Cameron, Johnson, & Camps, 1966;Ebbin, Gollub, Stein, & Wilson, 1969;Elmer & Gregg, 1967;Gregg & Elmer, 1969;Heifer & Pollock, 1967;Johnson & Morse, 1968;Nurse, 1964;Schloesser, 1964;Skinner & Castle, 1969). Elmer (1967) and Young (1964) add to Kempe's findings the factors of social and economic stress, lack of family roots in the community, lack of immediate support from extended families, social isolation, high mobility, and unemployment.…”
Section: Demographic Characteristicsmentioning
confidence: 82%
“…With physical injuries to young children it is difficult to establish whether the injury was inflicted or accidental. Indeed, several studies have suggested that accidents and abuse may have similar etiologies 9, 19 . In clinical practice, however, physical injuries are open to two very different interpretations: abuse or accident.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of abusive families, however, have not been demonstrated as substantially different from those within neglectful families 47 . Moreover, deciding whether an act is intentional or accidental often requires discerning the motivation of the perpetrator and evaluating all the other circumstances surrounding the incident 30 56 . “Act of commission” and “act of omission” also encounter the problem of evaluation and interpretation: not feeding a child would be an act of omission if caused by losing track of time, but an act of commission if punitively motivated.…”
Section: Child Maltreatmentmentioning
confidence: 99%